Modelling the Non-Linear Energy Intensity Effect Based on a Quantile-on-Quantile Approach: The Case of Textiles Manufacturing in Asian Countries - Muhammad Haseeb; Sebastian Kot; Hafezali Iqbal Hussain; Leonardus WW Mihardjo; Piotr Saługa (Energies, 2020)
The objective of the current examination is to identify the dynamic relationship between the textile industry and energy intensity. The study evaluates the asymmetric impact of textile manufacturing on energy intensity in leading Asian economies based on textile dominance. China, Indonesia, India, Pakistan, Bangladesh, Malaysia, South Korea, Thailand, Japan and Vietnam are dominant in textile manufacturing. In the present study we used yearly textiles and clothing data from top ten selected Asian textile manufacturing countries from 1990 to 2018. The results of quantile-on-quantile regression (QQ) confirmed that textiles and clothing (T&C) production have a positive and significant impact on energy intensity in all countries. The results further suggested that a low level of T&C production increases the level of energy intensity in all selected countries. On the other hand, the results of Granger causality in quantiles confirm a bidirectional causal relationship between T&C production and energy intensity in all selected countries except Thailand and Japan, where a uni-directional causal connection between textile and clothing manufacturing and energy intensity can also be found. This study recommends that governments and investors need to invest more in green and advanced technologies to reduce the energy intensity in Asian economies.